Cardiac dynamics: Alternans and arrhythmogenesis. Issue 5 (28th March 2016) - Tse, Gary; Wong, Sheung Ting; Tse, Vivian; Lee, Yee Ting; Lin, Hiu Yu; Yeo, Jie Ming
Abstract: Pre‐existing heterogeneities present in cardiac tissue are essential for maintaining the normal electrical and mechanical functions of the heart. Exacerbation of such heterogeneities or the emergence of dynamic factors can produce repolarization alternans, which are beat‐to‐beat alternations in the action potential time course. Traditionally, this was explained by restitution, but additional factors, such as cardiac memory, calcium handling dynamics, refractory period restitution, and mechano‐electric feedback, are increasingly recognized as the underlying causes. The aim of this article is to review the mechanisms that generate cardiac repolarization alternans and convert spatially concordant alternans to the more arrhythmogenic spatially discordant alternans. This is followed by a discussion on how alternans generate arrhythmias in a number of clinical scenarios, and concluded by an outline of future therapeutic targets for anti‐arrhythmic therapy.